2007
DOI: 10.1590/s0100-84042007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Atributos florais em um sistema de polinização especializado: Calathea cylindrica (Roscoe) K. Schum. (Marantaceae) e abelhas Euglossini

Abstract: -(Floral traits in a specialized pollination system: Calathea cylindrica (Roscoe) K. Schum. (Marantaceae) and Euglossini bees). Pollination specialization is promoted by floral features that favor pollinator fidelity and hinder the access to resources by other visitors. We investigated the pollination mechanism of one understory herb in southeastern Brazil. Calathea cylindrica flowers year-round and its flowers are peculiar because of the fusion and modification of some elements, asymmetry, secondary pollen pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…This aggregation and genetic profiling of living material is driving the developing concept of the metacollection (Griffith et al., 2019). Such living plant collections afford an excellent opportunity to investigate plant–animal interactions (Baretto & Freitas, 2007; Vasconcellos & Freitas, 2007), develop propagation protocols, and better understand the potential adaptability of plants to shifting climate regimes (Seal et al., 2017). Living fungal and microbial material is also now more readily available where excellent progress in aggregating collection information and sharing accession data has been made (Ryan, McCluskey, Verkleij, Robert, & Smith, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This aggregation and genetic profiling of living material is driving the developing concept of the metacollection (Griffith et al., 2019). Such living plant collections afford an excellent opportunity to investigate plant–animal interactions (Baretto & Freitas, 2007; Vasconcellos & Freitas, 2007), develop propagation protocols, and better understand the potential adaptability of plants to shifting climate regimes (Seal et al., 2017). Living fungal and microbial material is also now more readily available where excellent progress in aggregating collection information and sharing accession data has been made (Ryan, McCluskey, Verkleij, Robert, & Smith, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Scale bars = 15 and 1 cm in 7 and 8, respectively, and 1 mm in 9-12, tober to December (Groppo and Pirani 2005) and occurs along the swampy banks of a brooklet, whereas at the Rio de Janeiro collection site, the ornamental and invasive host plant species C, cylindrica blooms year-round and has an affinity for well-lit forest edges (Barreto and Freitas 2007), Identification and Imaging of Fly and Plant Taxa. Currently, the main forest remnant in Rio de Janeiro city is PNT, which covers =30 km^.…”
Section: Methodsmentioning
confidence: 99%
“…Forest areas are scarce (Barreto and Freitas, 2007;Leite and Machado, 2007;Sigrist and Sazima, 2015;D orea, 2018). Floral and reproductive biology studies of plants of the family Commelinaceae have reported awide variety of floral morphology among the genera (Evans et al, 2003;Kaul and Koul, 2008;Aona et al, 2011Aona et al, , 2014Aona et al, , 2016Aona et al, , 2022.…”
Section: Phenological Studies Of Herbaceous Species In Brazilian Atla...mentioning
confidence: 99%